Time Slows Down during Accidents - Arstila, Valtteri (Frontiers in Psychology, 2012)
The experienced speed of the passage of time is not constant as time can seem to fly or slow down depending on the circumstances we are in. Anecdotally accidents and other frightening events are extreme examples of the latter; people who have survived accidents often report altered phenomenology including how everything appeared to happen in slow motion. While the experienced phenomenology has been investigated, there are no explanations about how one can have these experiences. Instead, the only recently discussed explanation suggests that the anecdotal phenomenology is due to memory effects and hence not really experienced during the accidents. The purpose of this article is (i) to reintroduce the currently forgotten comprehensively altered phenomenology that some people experience during the accidents, (ii) to explain why the recent experiments fail to address the issue at hand, and (iii) to suggest a new framework to explain what happens when people report having experiences of time slowing down in these cases. According to the suggested framework, our cognitive processes become rapidly enhanced. As a result, the relation between the temporal properties of events in the external world and in internal states becomes distorted with the consequence of external world appearing to slow down. That is, the presented solution is a realist one in a sense that it maintains that sometimes people really do have experiences of time slowing down.